Windows-Based Special Applications Router - Athab, Omar A.; Hadi, Ahmed S.; Faraj, Sufyan T. (Al-Khwarizmi Engineering Journal, 2019)
The design and implementation of an active router architecture that enables flexible network programmability based on so-called "user components" will be presents. This active router is designed to provide maximum flexibility for the development of future network functionality and services. The designed router concentrated mainly on the use of Windows Operating System, enhancing the Active Network Encapsulating Protocol (ANEP). Enhancing ANEP gains a service composition scheme which enables flexible programmability through integration of user components into the router’s data path. Also an extended program that creates and then injects data packets into the network stack of the testing machine will be proposed, we will call this program the packet generator/injector (PGI). Finally, the success of the node architecture and its prototype implementation is evaluated by means of a few practical applications.